Subacute and Reproductive Oral Toxicity Assessment of the Hydroethanolic Extract of Jacaranda decurrens Roots in Adult Male Rats - Santos, Joyce Alencar; Arruda, Aline; Lima Cardoso, Claudia Andrea; Vieira, Maria do Carmo; Piccinelli, Ana Claudia; Santana Aquino, Diana Figueiredo de; Leite Kassuya, Candida Aparecida; Arena, Arielle Cristina [UNESP] (Hindawi Publishing Corporation, 2013)
Jacaranda decurrens subsp. symmetrifoliolata Farias & Proenc, a (Bignoniaceae) is a species traditionally used for the treatment of inflammatory and infectious diseases. Previous findings from our group reported scientifically that J. decurrens has anti-inflammatory efficacy. However, more toxicological studies are needed to support and ensure its safe use. The present study was carried out to evaluate the toxic effects of a prolonged treatment with hydroethanolic root extract of J. decurrens (EJD) on hematological, biochemical, and reproductive parameters in adult male rats. The animals received by oral gavage 0; 250; 500; or 1000 mg/kg body weight of EJD for 28 days. After the treatment, biochemical, hematological, histopathological, and reproductive parameters were analyzed. The EJD treatment did not cause adverse effects on body weight gain, feed and water consumption, hematological and biochemical profiles, or histopathological analysis of liver and kidney. Similarly, there were no statistically significant differences in reproductive parameters, such as sperm production, number of sperm in the epididymis, and sperm morphology. These results demonstrate the absence of subacute toxicity as a result of the oral treatment with EJD for 28 days in adult male rats. However, other studies should be performed to evaluate the total safety of this plant.